Criticism of the Existence of Political Parties in the National Long Term Development Plan - Waruwu, Yafeti (Pancasila International Journal of Applied Social Science, 2023)
The existence of law aims to provide security and order and guarantee the existence of welfare that is obtained by the community from the State as the umbrella of society. Rules of law in addition to human interests against the dangers that threaten them, also regulate the relationship between humans. A society that is developing rapidly within the state is influenced by the changing times, so that needs must be met according to the times. For this reason, contextual law is needed in the sense that it can accommodate social practices in society by being regulated by legal norms. Legal teachings that can be applied in order to create a correlation between law and society, namely social laws that are stronger and more advanced than teachings created by individual law. This legal articulation will create a law that is in accordance with the aspirations of the community, therefore the estuary of law is not only justice and legal certainty, but the aspect of expediency must also be fulfilled.